2013
DOI: 10.3724/sp.j.1042.2013.01248
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Studies of the Dark Triad

Abstract: The studies on the Big Five represent the exploration into non-clinical personalities, whereas the studies on the Dark Triad represent the exploration into the shadow of the subclinical personalities. The Dark Triad is composed of three personality traits: Machiavellianism, narcissism and psychopathy, which are usually defined as antisocial personalities in the western culture. Results of recent studies on the Dark Triad indicate: (1) Machiavellianism, narcissism and psychopathy are independent yet intertwinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Therefore, personality traits are consistent with individual life history strategies (Figueredo, Vásquez, Brumbach, & Schneider, 2007; Figueredo et al, 2005), and studies have empirically proven that Dark Triad personality traits are linked to life history strategy (Figueredo et al, 2005; Jonason et al, 2010). Specifically, life history theory emphasizes the long-term role of the environment in shaping personality; thus, the Dark Triad is no longer a group of personality traits of “maladjustment” and “need for treatment” but the result of an individual’s active adaptation to the environment (Qin & Xu, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, personality traits are consistent with individual life history strategies (Figueredo, Vásquez, Brumbach, & Schneider, 2007; Figueredo et al, 2005), and studies have empirically proven that Dark Triad personality traits are linked to life history strategy (Figueredo et al, 2005; Jonason et al, 2010). Specifically, life history theory emphasizes the long-term role of the environment in shaping personality; thus, the Dark Triad is no longer a group of personality traits of “maladjustment” and “need for treatment” but the result of an individual’s active adaptation to the environment (Qin & Xu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research has shown that the Dark Triad personality traits can at least partially develop due to environmental causes (Barlett, 2016; Qin & Xu, 2013). Family is the principal environment in which human development takes place and has been shown to influence Dark Triad personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…The result also showed that psychopathy was a stronger predictor of Internet adaptation than Machiavellianism or narcissism. One possible reason is that individuals with high psychopathy are impulsive, lack of empathy and responsibility (Qin and Xu, 2013) and have negative social adaptation characteristics (Repacholi et al, 2003). Since Internet adaptation is a special kind of social adaptation, it should be highly correlated with psychopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional personality traits (e.g., Big Five personality traits) are widely accepted, they excessively focus on the “bright” aspects of personality and lack consideration for the “impolite” aspects of personality (Block, 2010). Recently, Dark Triad traits were developed to make up for the limitations of traditional personality research and have gradually been noticed in China (Stead et al, 2012; Qin and Xu, 2013; Zhang and Zhang, 2014). There is little doubt that the Dark Triad traits represent three related traits: Machiavellianism, psychopathy and narcissism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation